اثر كفاءة نظم المعلومات المحاسبية على جودة التقارير المالية في البنوك السودانية - mohammed, hassan bashier hassan; العاقب, آمال محمد; يوسف, مصطفي محمد (Gezira Journal of Economic and Social Sciences; Vol 11 No 1 (2020), 2022)
المستخلص تتمثل مشكلة الدراسة في سؤال رئيسي اثر كفاءة نظم المعلومات المحاسبية على جودة التقارير المالية في البنوك السودانية  هدفت الدراسة الى التعرف على مكونات نظم المعلومات المحاسبية المستخدمة في البنوك السودانية العاملة في ولاية الجزيرة وأثر على جودة التقارير المالية من حيث؛ البعد الشكلي للمعلومات، بعد محتوى للمعلومات ، والبعد الزمني للمعلومات. استخدم الباحثون المنهج الوصفي في تغطية الاطار النظري وعرض الدراسات السابقة والمنهج التحليلي الميداني وذك بواسطة استبانة مكونة من 23 عنصر حيث تم  توزيعها على عينة من البنوك العاملة بولاية الجزيرة بواسطة عينة طبقية. قام الباحثون بتفريغ وتحليل الاستبانة من خلال برنامج الحزم الإحصائية للعلوم الاجتماعية (spss). وتم استخدام الاحصاءات؛ التكرارات والنسب المئوية، الوسط الحسابي، ومعامل ارتباط الرتب سبيرمان Spearman.اهم نتائج الدراسة توجد علاقة ذات دلالة احصائية بين كفاءة نظم المعلومات المحاسبية وجودة التقارير المالية  بالبنوك السودانية. وكذلك توجد علاقة إيجابية بين كفاءة نظم المعلومات المحاسبية وبين؛ البعد الشكلي للتقارير المالية، بعد المحتوى للتقارير المالية، و بعد الزمني للتقارير المالية. وتوصي الدراسة بضرورة الاهتمام بمكونات نظم المعلومات المحاسبية المستخدمة في البنوك السودانية، وكذلك ضرورة الاهتمام بالبعد الشكلي للمعلومات في التقارير المالية في البنوك السودانية.   Abstract The study problem is represented in a major question: the effect of the efficiency of Accounting Information Systems (AIS) on the quality of financial reports in Sudanese banks. The study aimed to identify the components of (AIS) used in Sudanese banks operating in the state of the island and the effect on the quality of financial reports in terms of: The formal dimension of information, the dimension of content for information, and the temporal dimension of information . The researchers used the descriptive approach in covering the theoretical framework and presenting the previous studies and the field analytical method. This was done by means of a questionnaire consisting of 23 elements, which was distributed to a sample of banks operating in the state of the island by stratified sample. The researchers unpacked and analyzed the questionnaire through the Statistical Package for Social Sciences (SPSS) program. Statistics were used; Frequencies, percentages, arithmetic mean, and Spearman's rank correlation coefficient. The most important results of the study There is a statistically significant relationship between the efficiency of (AIS) and the quality of financial reports in Sudanese banks. There is also a positive relationship between the efficiency of (AIS) and: The formal dimension of the financial reports, the content dimension of the financial reports, and the temporal dimension of the financial reports. The study recommends the need to pay attention to the components of (AIS) used in Sudanese banks, as well as the need to pay attention to the formal dimension of information in financial reports in Sudanese banks. Key words : accounting information systems; Quality of financial reports; Sudanese banks